PENGARUH PENERAPAN GREEN ACCOUNTING DAN IMPLEMENTASI SUSTAINABILITY REPORTING TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI : (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2021 – 2024) - Melisa Sari Kano; Bill Pangayow; Yulianti Karoma; Alfiana Antoh (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
This study examines the effect of Green Accounting and Sustainability Reporting on corporate financial performance with Good Corporate Governance as a moderating variable in mining companies listed on the Indonesia Stock Exchange during 2021–2024. A quantitative causal associative approach was employed. The sample consisted of 11 companies with 44 observations selected through purposive sampling. Financial performance was measured using Return on Assets (ROA). Green Accounting was measured through environmental cost disclosure analysis, Sustainability Reporting through a CSR Disclosure Index based on GRI Standards, and Good Corporate Governance was proxied by the audit committee. Panel data regression and Moderated Regression Analysis (MRA) were applied using EViews 12. Green AccountingThe results indicate that Green Accounting and Sustainability Reporting do not significantly affect ROA directly. However, Good Corporate Governance strengthens the relationship between sustainability practices and financial performance. These findings suggest that corporate governance mechanisms play a crucial role in translating sustainability initiatives into financial outcomes.